Slave Exploitation and its Types in Eastern Islamic Societies With Special Emphasis on the Sâmânîds (9th/10th Century) - Erkoç, Murat (Fırat University, 2025)
The main purpose of this study is to approach the production and types of slavery, which constituted the basis of economic life in the S?m?nids, from a historical perspective, taking into consideration the political situation of the Eastern Islamic world in the 9th/10th century. When we examine various periods of human history, the institution of slavery varies according to time and place depending on the impact of environmental conditions. The acceleration of the slave trade in Eastern Islamic societies began with the Samanids establishing dominance in Khorasan and Transoxiana. Slave transit operations were carried out in the societies of Transoxiana, Khorasan, Khwarezm, India, China, Turkish countries, Sakalibe, Iraq, Damascus and other regions from the Arabian peninsula (Arabia). The importance given to the trade of white slaves for military and political employment during the Abbasid period corresponds to the Samanids. As a matter of fact, laws containing orders and prohibitions regarding trade were prepared during this period. Bukhara, Samarkand and Khwarazm in the Turkestan region stood out as centers of slave trade. In these cities where large commercial fairs were held, the slaves were trained and sold after being taught Islamic etiquette. It was discussed that the prices of slaves varied according to their skin color.

Bu araştırmanın esas amacı 9./10. yüzyılda Doğu İslâm dünyasının siyasi durumu dikkate alınarak Sâmânîler özelinde iktisadi hayatın temelini oluşturan köleliğin istihsali ve çeşitlerine tarihsel bir bakış açısı ile yaklaşmaktır. İnsanlık tarihinin çeşitli dönemlerini incelediğimizde kölelik müessesesi çevre koşullarının etkisi ile zaman ve mekâna göre farklılık göstermektedir. Köle ticaretinin Doğu İslam toplumlarında ivme kazanması Sâmânîlerin Horasan ve Mâverâünnehr’de hâkimiyet kurmasından sonra başlamıştır. Köle transit işlemleri; Mâverâünnehr toplumlarında, Horasan, Hârizm, Hindistan, Çin, Türk ülkeleri, Sakâlibe, Irak, Şam ve Arap yarımadası (Arabistan)’ndan diğer bölgelere kadar yapılmıştır. Abbasiler dönemi ile askeri ve siyasi açıdan istihdam edilen beyaz kölelerin ticaretine ehemmiyet gösterilmesi Sâmânîlere tekabül etmektedir. Nitekim ticarete yönelik emir ve yasakların yer aldığı kanunların bu dönemde hazırlandığı görülmektedir. Türkistan sahasındaki Buhara, Semerkant ve Hârizm köle ticaretinin yapıldığı merkezler olarak öne çıkmışlardır. Büyük ticari panayırların kurulduğu bu şehirlerde kölelerin terbiyesi yapılıp, İslâm adabı öğretildikten sonra satılmışlardır. Çalışmada kölelerin ten renklerine göre fiyatlarının değişkenlik gösterdiği ele alınmıştır.
Sâmânîler Özelinde Doğu İslâm Toplumlarında Köle İstihsâli ve Çeşitleri (9./10. Yüzyıl)
Keywords: General Turkish History (Other); Genel Türk Tarihi (Diğer)